Chia (Salvia hispanica L.) Seed Oil Supplementation to the Diet: Effects on in Vitro Rumen Fermentation Characteristics and Lipid Biohydrogenation - Selma Büyükkılıç Beyzi; Murat Say (Veterinary Medicine and Science)
ABSTRACT The study investigated the effects of chia seed oil supplementation on the diet with different levels of in vitro ruminal biohydrogenation and fermentation. The treatment groups were control (no additional oil) or the addition of 10, 20 and 30 g/kg of chia seed oil in the diet as DM based. The treatment groups were incubated using a batch culture technique, and the fermentation terminated after 6, 12, and 24 h. The biohydrogenation rate of unsaturated fatty acids varied between 71% and 98% after 24‐h incubation. Biohydrogenation of C18:2 and C18:3 fatty acids decreased in treatment groups. The C18:0, t11 C18:1 and c9 c12 C18:2 n‐6, total conjugated linoleic acid (CLA) and cis‐9, trans‐11 CLA fatty acids increased linearly with chia seed oil supplementation. In addition, the highest CLA content was obtained from the 20, and 30 g/kg of chia seed oil‐supplemented groups. The chia seed oil supplementation did not affect ruminal fermentation parameters. Under the current in vitro study conditions, chia seed oil supplementation to diet increased linearly the ruminal biohydrogenation intermediate products such as total CLA and trans‐11 C18:1 fatty acid and decreased linearly the ruminal biohydrogenation ratio of C18:3 n‐3 fatty acid. Supplementing chia seed oil can be a useful nutritional tool for increasing CLA, vaccenic acid, and n‐3 PUFA fatty acids potentially beneficial to human health.